2019
DOI: 10.1177/2192568218816981
|View full text |Cite
|
Sign up to set email alerts
|

The Safety Profile of Percutaneous Minimally Invasive Sacroiliac Joint Fusion

Abstract: Study Design:Literature review.Objectives:Systematic review of the existing literature to determine the safety of minimally invasive (MI) sacroiliac (SI) joint fusion through the determination of the rate of procedural and device-related intraoperative and postoperative complications.Methods:All original studies with reported complication rates were included for analysis. Complications were defined as procedural if secondary to the MI surgery and device related if caused by placement of the implant. Complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…However, a German study of 1.37 million anaesthetic procedures with elective patients, graded as ASA classification physical status I and II, showed 7.3 cases of death or serious complication per million cases, corresponding to a very low risk ( 41 ). All types of surgery are associated with risks of complications, and so also for MIS SIJ ( 42 ). In the control group the risks for surgical complications should be very low.…”
Section: Discussionmentioning
confidence: 99%
“…However, a German study of 1.37 million anaesthetic procedures with elective patients, graded as ASA classification physical status I and II, showed 7.3 cases of death or serious complication per million cases, corresponding to a very low risk ( 41 ). All types of surgery are associated with risks of complications, and so also for MIS SIJ ( 42 ). In the control group the risks for surgical complications should be very low.…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review on the safety profile of percutaneous minimally invasive SI joint fusion looking at 14 studies that included 720 complications found a complication rate of 11.1% (8). The most common complication was wound infection, but 3.05% of the complications were secondary to placement of the implant, with nerve root impingement being the most common result.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The economic burden of treatment is significant, with an average cost per patient of $63,913. 10 SIJF has been demonstrated to significantly improve pain, disability, and quality of life in several retrospective studies [1][2][3]7 and three randomized controlled trials. [4][5][6] Revision rates for SIJF are acceptably low, ranging from 0% to 17% with a mean of 6% in a review by Cleveland et al 1 Two meta-analyses cited rates of 2.1% and 2.6% across 432 and 720 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Revision rates for SIJF are acceptably low, ranging from 0% to 17% with a mean of 6% in a review by Cleveland et al 1 Two meta-analyses cited rates of 2.1% and 2.6% across 432 and 720 patients, respectively. 7,11 Because arthrodesis may take more than 1 year to occur, 3 less obvious malpositioning that is not immediately addressed may prolong pain and disability for more than 12 months. Robot-assisted platforms for SIJF may prevent inaccuracy given their reproducibility of trajectory and advantage over conventional fluoroscopy for anatomically challenging areas, such as the pelvis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation